Writing Photography: The Grandmother in Remembrance of Things Past, the Mother in Camera Lucida, and Especially, the Mother in The Lover - Erin Mitchell (Studies in 20th & 21st Century Literature, 2000)
Proust, Barthes, and Duras describe photographs of maternal figures. Such photographs are not reproduced, but witheld or nonexistent. I include the Proustian narrator's imagined photograph of his grandmother; Barthes's unreproduced photo of his mother at five years old standing in the Winter Garden; and, the Durasien narrator's imagined photograph of her mother, Marie Legrand, in virtual photography. I explore the effects, in these instances, of virtual photography of maternal figures. Like actual photography, virtual photography implies that a referent exists for the image; like actual photography, virtual photography immobilizes, objectifies, and kills its referent even as it arrests the dying of that referent. Like actual photography, virtual photography can figure a recurring moment of separation from and mourning for the photographed person. Unlike actual photography, however, virtual photography creates "absolutes"; the actual image is rescued from the use and gaze of the public, who may not love the person imaged. These writers thus control the interpretation of the image, and contain its excesses while protecting writing itself from the threat of the image.
Keywords: Proust; Barthes; Duras; maternity; maternal figures; grandmother; virtual photography; photography; absolutism; absolutes; Winter Garden; Durasien; Marie Legrand; referent; separation; mourning